Factors Affecting Beef Volume Imports From Australia - Endang Sulistiyani; Juliarti Mega Pertiwi; Luqman Khakim (AFEBI Management and Business Review, 2022)
The aim of this study is to analyze the influence of consumption, production and gross domestic product on the volume of beef import from Australia in period 2010- 2019. This research applied explanatory research method with quantitative approach. The data sources collected from Badan Pusat Statistik (BPS) and trademap.org. The sample in this research is determined by purposive sampling The study explored with multiple linear regression statistical analysis. The result showed that consumption had insignificant effect on the volume of beef import partially. Meanwhile, production had significant negative effect on the volume of beef import. Gross domestic product also had partial significant positive effect on the volume of beef import.